Health-related quality of life in 153 children with neuromuscular disorders in Latin America: is it age, functional dependence or diagnosis? - Ortega, Javiera (2024)
Fil: Ortega, Javiera. Pontificia Universidad Católica Argentina. Facultad de Psicología y Psicopedagogía. Centro Investigaciones de Psicología y Psicopedagogía; Argentina